e-Finance : the electronic revolution - Banks, Erik. (Chichester ; New York : J. Wiley, 2001)
This book explains clearly and concisely how and why the world of retail and institutional finance has started a migration from conventional foundations to computerized, internet-driven practices, and considers where such efforts will ultimately lead.
Includes bibliographical references (p. [199]-200) and index.
gau 18/06/14 uaj 20/02/2015
Loans
Keywords: Electronic commerce; Financial services industry; Internet